2023
DOI: 10.3390/polym15173497
|View full text |Cite
|
Sign up to set email alerts
|

Strong Bioactive Glass-Based Hybrid Implants with Good Biomineralization Activity Used to Reduce Formation Duration and Improve Biomechanics of Bone Regeneration

Jing Chen,
Yonglei Xing,
Xiaozhuan Bai
et al.

Abstract: Developing bioactive implants with strong mechanical properties and biomineralization activity is critical in bone repair. In this work, modified cellulose nanofiber (mCNF)-reinforced bioactive glass (BG)-polycaprolactone (PCL) hybrids (mCNF–BP) with strong biomechanics and good apatite formation ability were reported. Incorporating mCNFs shortens the forming duration of the hybrid films and enhances the biomechanical performance and in vitro apatite-formation capability. The optimized biomechanical performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They have found applications in orthopedics, dentistry, and even drug delivery [48][49][50][51]. By changing the content of the main components, such as sodium dioxide, calcium oxide, and phosphorus, bioactive glasses with different properties can be developed [47,[52][53][54]. In addition, many in vitro and in vivo, studies on bioglass have shown that this material can be used to produce scaffolds for tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…They have found applications in orthopedics, dentistry, and even drug delivery [48][49][50][51]. By changing the content of the main components, such as sodium dioxide, calcium oxide, and phosphorus, bioactive glasses with different properties can be developed [47,[52][53][54]. In addition, many in vitro and in vivo, studies on bioglass have shown that this material can be used to produce scaffolds for tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hydroxyapatite (HA) stands out as the most commonly employed biomaterial for fabricating these artificial implant skeletons. Following bone reconstruction surgery involving porous HA skeletons, bodily fluids come into contact with and gradually infiltrate these structures, initiating biomineralization [3][4][5][6]. Apatite nanocrystals are slowly formed after the beginning of biomineralization.…”
Section: Introductionmentioning
confidence: 99%